2003
DOI: 10.1104/pp.102.018069
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of Self-Incompatibility in a Natural Population ofPetunia axillaris Caused by Loss of Pollen Function

Abstract: Although Petunia axillaris subsp. axillaris is described as a self-incompatible taxon, some of the natural populations we have identified in Uruguay are composed of both self-incompatible and self-compatible plants. Here, we studied the selfincompatibility (SI) behavior of 50 plants derived from such a mixed population, designated U83, and examined the cause of the breakdown of SI. Thirteen plants were found to be self-incompatible, and the other 37 were found to be selfcompatible. A total of 14 S-haplotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…In Campanula rapunculoides, analyses of 31 parental families suggested the presence of 3-5 unlinked, mostly recessive genetic modifiers affecting the strength of the SI response (GoodAvila and Stephenson 2002). In P. axillaris, the presence of self-compatible plants has been shown to be due to three different mechanisms: a linked gene that suppresses the expression of a specific S-RNase gene (Tsukamoto et al 2003a), a loss of function on the pollen component of SI (Tsukamoto et al 2003b), and the presence of unlinked modifiers (Tsukamoto et al 1999). The variable strength of SI has been shown in most cases in species with small patchy populations such as weeds (Baker 1965), island colonizers (Bateman 1952;Burd 1994), and populations growing in peripheral habitats (Busch 2005); these populations typically undergo repeated events of colonization and local extinction and usually consist of a small number of individuals and are likely to experience reduced pollinator and mate availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Campanula rapunculoides, analyses of 31 parental families suggested the presence of 3-5 unlinked, mostly recessive genetic modifiers affecting the strength of the SI response (GoodAvila and Stephenson 2002). In P. axillaris, the presence of self-compatible plants has been shown to be due to three different mechanisms: a linked gene that suppresses the expression of a specific S-RNase gene (Tsukamoto et al 2003a), a loss of function on the pollen component of SI (Tsukamoto et al 2003b), and the presence of unlinked modifiers (Tsukamoto et al 1999). The variable strength of SI has been shown in most cases in species with small patchy populations such as weeds (Baker 1965), island colonizers (Bateman 1952;Burd 1994), and populations growing in peripheral habitats (Busch 2005); these populations typically undergo repeated events of colonization and local extinction and usually consist of a small number of individuals and are likely to experience reduced pollinator and mate availability.…”
Section: Discussionmentioning
confidence: 99%
“…One possible target may lie on the flanking regions surrounding different S-alleles. These sequences are known to be highly divergent (Coleman and Kao 1992); therefore, it could be possible for specific regulatory proteins to be either required for the appropriate transcription of different S-alleles or involved in the turnover of specific RNA transcripts (Tsukamoto et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…One possible role of the modifier genes is to regulate the expression of the S-locus genes. For example, Tsukamoto et al (1999Tsukamoto et al ( , 2003 found that several pistil-part self-compatible plants identified from a natural population of self-incompatible Petunia axillaris carried a defective S 13 -haplotype (designated S 13 sps ), which did not produce any transcript of the S 13 -RNase gene. They further showed that self-incompatible progeny homozygous or heterozygous for the functional S 13 -haplotype were obtained from self-pollination of the self-compatible plants that carried the S 13 sps S 15 genotype.…”
Section: Other Genes That Modulate the Si Responsementioning
confidence: 99%
“…The system can be lost secondarily, resulting in transition to self-compatibility (SC) by mutations linked to the Slocus (Broothaerts et al, 2004;de Nettancourt, 2001), by the presence of pollen heteroallelic for the Sgenotype, which may be the result of polyploidization (Entani et al, 1999), or by modifier gene(s) unlinked to the S-locus (Tsukamoto et al, 2003).…”
Section: Introductionmentioning
confidence: 99%